COMMUNITY NURSERY PARTICIPATION FOR AVAILABILITY OF SEEDS IN CANDI REJO VILLAGE BIRU BIRU SUB-DISTRICT DELI SERDANG DISTRICT - Rahmawaty; Yunus Afifuddin; Ridahati Rambey (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The community service activity was conducted in Candi Rejo Village, Biru-biru District, Deli Serdang Regency, North Sumatra Province. This activity aimed to ensure the availability of seeds at the farm level by providing assistance to community nurseries. The types of plants that were seeded such as: coconut, durian, avocado, mindi and cocoa. The five types of plants were needed by the local community. Agroforestry (combining cocoa and wood species such as mindi, coconut, avocado, durian and others) was a system used by the Candi Rejo Village community.